2011
DOI: 10.1097/ta.0b013e3181f31e37
|View full text |Cite
|
Sign up to set email alerts
|

Does CT Evidence of a Flat Inferior Vena Cava Indicate Hypovolemia in Blunt Trauma Patients With Solid Organ Injuries?

Abstract: CT evidence of FI is a good indicator of hypovolemia and an accurate predictor for prognosis in trauma patients with blunt solid organ injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Regardless of the use of mechanical ventilation, the IVC was found to be FLAT before resuscitation and changed to FAT after fluid resuscitation, suggesting that fluid administration was responsible for the change. In a recent manuscript, Liao et al 15 found the presence of a FLAT IVC in computerized tomography to be a good indicator of hypovolemia and an accurate predictor for prognosis in trauma patients with blunt solid organ injuries. In this study, attendings were able to estimate IVC diameter and diameter change after fluid bolus without M-mode measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the use of mechanical ventilation, the IVC was found to be FLAT before resuscitation and changed to FAT after fluid resuscitation, suggesting that fluid administration was responsible for the change. In a recent manuscript, Liao et al 15 found the presence of a FLAT IVC in computerized tomography to be a good indicator of hypovolemia and an accurate predictor for prognosis in trauma patients with blunt solid organ injuries. In this study, attendings were able to estimate IVC diameter and diameter change after fluid bolus without M-mode measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have described this concept, but none of them have confirmed this finding in the geriatric population. 3 Although patients presenting with an FI were more likely to die, not all patients in shock presented with an FI. This is different from previous studies noting this relationship in younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…1 A flat IVC (FI) has been associated with shock and mortality in young trauma patients (age G 55 years). 2,3 Patients with a smaller anteroposterior (AP) diameter of the IVC on imaging require increased amounts of fluid, blood transfusions, and vascular support to maintain their physiology. This evidence supports the correlation between an FI and hypovolemic shock.…”
mentioning
confidence: 99%
“…10 All these ambivalent findings could potentially mask shock and delay adequate resuscitation. Early recognition of clinical hemodynamic instability and tissue hypoperfusion is critical in optimizing treatment and improving outcomes; however, determining the amount of blood loss accurately is difficult since there is no tool to assess ongoing blood loss, especially when this is caused by bleeding to the body cavities/ compartments and the retroperitoneum.…”
Section: Discussionmentioning
confidence: 99%
“…Often, the initial assessments of the trauma patient include FAST [Focused Assessment with Sonography in Trauma] examination. 2,10,19,20 Trauma patients with intra-abdominal injuries can have an associated intra-abdominal hemorrhage. 15 Although the practice of using FAST is still taught and recommended in the ATLS as a screening tool for triaging blunt trauma patients, its utility has been questioned.…”
Section: Discussionmentioning
confidence: 99%